2022
DOI: 10.1063/5.0067214
|View full text |Cite
|
Sign up to set email alerts
|

Physics of the high specific impulse alternative low power hybrid ion engine (alphie): Direct thrust measurements and plasma plume kinetics

Abstract: The Alternative Low Power Ion Engine (alphie) is a high specific impulse plasma thruster different from conventional gridded ion engines (GIEs). It uses only one external cathode and ions and electrons flow through the open spaces of its two grids, whereas only ions are transported through the GIE ion optics. Ionizing electrons from the cathode move inward to the alphie ionization chamber and ions, which are neutralized by electrons from the same cathode, exit along the opposite direction. These currents toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…In other words, there are two types of electrons in the steady-state ion thruster plume: thermal electrons trapped around the plume core and electrons flowing downstream driven by the potential gradient. These two distributions were also seen in the experiment of Conde et al [11], who identified low-energy and highenergy groups.…”
Section: Effect Of Space Vs Ground-based Chamber Conditionssupporting
confidence: 69%
See 4 more Smart Citations
“…In other words, there are two types of electrons in the steady-state ion thruster plume: thermal electrons trapped around the plume core and electrons flowing downstream driven by the potential gradient. These two distributions were also seen in the experiment of Conde et al [11], who identified low-energy and highenergy groups.…”
Section: Effect Of Space Vs Ground-based Chamber Conditionssupporting
confidence: 69%
“…In reality, the apertures cause variations in ion density, and electrons present to some extent inside the aperture [14, 42]. Unlike a hollow cathode, electrons are emitted from the neutralizer wall surface similar to a filament neutralizer [10,11], a direct emission neutralizer [43], or a diode mode neutralizer [44]. Collisions between Xe and e − , Coulomb collisions between Xe + and e − , the presence of multiply-charged ions (i.e.…”
Section: Calculation Geometry and Speciesmentioning
confidence: 99%
See 3 more Smart Citations